2021
DOI: 10.14710/jbs.30.2.154-172
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Keadilan Organisasional Terhadap Kinerja Karyawan Dimediasi LMX (Leader-Member Exchange) Dilihat dari Aspek Gender

Abstract: The purpose of this article is to examine the mediating role of leader-member exchange in the relationship between organizational justice and employee performance in terms of gender. This article focuses on ATLM (Medical Laboratory Technologist) regarding organizational justice practices and the Leader-Member Exchange relationship and how these perceptions predict employee performance and how it affects employee gender. The sample used was 191 ATLM in type C hospitals in the D.I. Yogyakarta and Central Java. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…This needs to be done so that organizational justice can strengthen the influence of leader-member exchange on performance. Thus, this study can complement the previous research conducted by Nareri et al (2022), Widya et al (2021), and Kurniawan & Rijanti (2023). So, it can be concluded that the fourth hypothesis (H4) is accepted.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This needs to be done so that organizational justice can strengthen the influence of leader-member exchange on performance. Thus, this study can complement the previous research conducted by Nareri et al (2022), Widya et al (2021), and Kurniawan & Rijanti (2023). So, it can be concluded that the fourth hypothesis (H4) is accepted.…”
Section: Resultssupporting
confidence: 84%
“…A high or good leader-member exchange (LMX) can be built when employees and leaders feel that there is equality in the distribution of benefits obtained by the organization. Conversely, injustice will create tension and work tension between employees and even with leaders, so that performance will be greatly disrupted (Widya et al, 2021). Organizational justice is an important factor that influences work attitudes and behavior which in turn can grow performance (Kurniawan & Rijanti, 2023).…”
Section: Moderation Of Organizational Justice On the Influence Of Lea...mentioning
confidence: 99%
“…Organizational justice has no effect to employee performance, these results are in line with research conducted by Widya et al (2021) which states that organizational justice has no significant effect on employee performance. When employees feel fair treatment in resource distribution, decision-making policies and interpersonal interactions in the work environment can increase motivation and job satisfaction.…”
Section: Structural Model Testing or Hypothesis Testing (Inner Model)supporting
confidence: 88%
“…Sehingga persepsi keadilan organisasional yang mereka rasakan, tidak akan banyak berpengaruh terhadap perilaku etis yang mereka tunjukkan. Keadilan organisasional ternyata tidak selalu memberi pengaruh positif yang signifikan terhadap karyawan (Kumasey et al, 2021), kecuali bila melibatkan variabel mediasi lainnya (Widya et al, 2021;Pan et al, 2018). Hal ini mengisyaratkan bahwa keadilan organisasional harus dapat melahirkan sebuah kondisi yang tertentu agar mampu memberi pengaruh positif yang berarti terhadap karyawan.…”
Section: H3unclassified